Analysis of Fluorescence Spectra of Citrus Polymethoxylated Flavones and Their Incorporation into Mammalian Cells - Gonçalves, Danielle R. [UNESP]; Manthey, John A.; Da Costa, Paulo I. [UNESP]; Rodrigues, Marilia C. M. [UNESP]; Cesar, Thais B. [UNESP] (American Chemical Society (ACS), 2018)
Citrus polymethoxylated flavones (PMFs) influence biochemical cascades in human diseases, yet little is known about how these compounds interact with cells and how these associations influence the actions of these compounds. An innate attribute of PMFs is their ultraviolet-light-induced fluorescence, and the fluorescence spectra of 14 PMFs and 7 PMF metabolites were measured in methanol. These spectra were shown to be strongly influenced by the compounds' hydroxy and methoxy substituents. For a subset of these compounds, the fluorescence spectra were measured when bound to human carcinoma Huh7.5 cells. Emission-wavelength maxima of PMF metabolites with free hydroxyl substituents exhibited 70-80 nm red shifts when bound to the Huh7.5 cells. Notable solvent effects of water were observed for nearly all these compounds, and these influences likely reflect the effects of localized microenvironments on the resonance structures of these compounds when bound to human cells.
Keywords: citrus; Huh7.5 cells; metabolites; nobiletin; pyrylium; resonance; Rutaceae; sinensetin; solvent effects; tangeretin